The Positive Impact of Digital Literacy on Science Process Skills - Darmaji; Astalini; Dwi Agus Kurniawan; Minarsih; Rahmat Perdana (Universitas Pendidikan Ganesha, 2023)
Students' science process skills are important to improve, one of which is by using technology so that students' digital literacy skills are also needed in using technology. The purpose of this study was to analyze the effect of digital literacy on science process skills. The type of research used is a mix method with a sequential explanatory model. The population in sthis study were students in class X MIPA at senior high school. The sampling technique used was simple random sampling and a sample of 50 students was obtained and the instruments included questionnaires, observations and teacher interviews. Quantitative data were obtained from questionnaires and observations while qualitative data were obtained from interviews. After the research is done, the data will be analyzed. Quantitative data analysis used statistical tests, namely descriptive statistics and parametric inferential statistics. Descriptive statistical analysis is presented in tabular form in the form of frequency, mean, median, max value and min value while inferential parametric analysis is in the form of a t test with prerequisite tests: normality test and linearity test. While the qualitative data uses Miles & Huberman. The research results obtained were that digital literacy had an effect on science process skills with a percentage of 93.5%.